Zircon Hf isotopic constraints on magmatic and tectonic evolution in Iran: Implications for crustal growth in the Tethyan orogenic belt. (1st September 2017) - Chiu, Han-Yi; Chung, Sun-Lin; Zarrinkoub, Mohammad Hossein; Melkonyan, Rafael; Pang, Kwan-Nang; Lee, Hao-Yang; Wang, Kuo-Lung; Mohammadi, Seyyed Saeid; Khatib, Mohammad Mahdi
Graphical abstract: Highlights: Zircons from major magmatic domains of Iran are analyzed for U-Pb-Hf isotopic compositions. Magmatic rocks during the past ∼600 Myr have variable zircon Hf isotopic features. The majority of magmatic zircons are highly radiogenic in terms of Hf isotopic compositions. Mantle input played a significant role in the magmatic genesis and crustal growth. Abstract: This study presents coupled zircon U-Pb and Hf isotopic analyses of 82 igneous rocks that are mainly from the Urumieh-Dokhtar magmatic arc (UDMA) and Sanandaj-Sirjan zone (SSZ), Iran, together with additional 11 samples from Armenia, along the central part of the Neotethyan orogenic belt. The results provide an overview of the isotopic variations for several important magmatic stages, which can improve our understanding of magmatic and crustal evolution regarding the life cycles of Tethys oceans during the past ∼600 Myr in Iran and adjacent regions. Late Neoproterozoic-Cambrian (595–511 Ma) basement rocks in the SSZ and Central Iran, which were part of the Cadomian magmatic arc, yield zircon εHf (T) values from +11 to −3 and are attributed to have partially evolved with juvenile magmas in the Arabian-Nubian Shield along the northern margin of Gondwana. Carboniferous (349–311 Ma) A-type granitoids in the northwestern SSZ show mostly positive zircon εHf (T) values from +5 to −1, and they are interpreted as the product involving a moderate mantle contribution in an extensional environment affiliated with the initial rifting of the Neotethys. Late Triassic (219–203 Ma) granitoids in the eastern Alborz give slightly lower zircon εHf (T) values between +3 and −3 as a result of the progress of closing the Paleotethys. Middle Jurassic (∼165 Ma) granitoids in the SSZ and Central UDMA, representing an early phase of Neotethyan subduction-related magmatism, exhibit similar zircon εHf (T) values from +5 to −3, implying an origin of mixed juvenile and reworked sources to form the magmas. Late Cretaceous (81–72 Ma) intrusive rocks in the Southeast UDMA yield bimodal zircon εHf (T) values from +15 to +11 in the Jiroft and from +5 to −9 in the Bazman areas, suggesting that the latter involves a reworked crustal component. At the latest Cenozoic, magmatic rocks with ages <55 Ma that occurred widely across Iran and Armenia before and after the Arabia-Eurasia collision give dominantly positive zircon εHf (T) values ranging between +15 and −1, except for the Eocene granitoids in Central Iran, which have remarkably lower zircon εHf (T) values down to −7. Therefore, these Cenozoic rocks yield younger zircon Hf crustal model ages (TDM C ), mainly from ca. 1.2 to 0.2 Ga, than the Late Neoproterozoic-Mesozoic rocks. As the whole, the highly radiogenic Hf isotopes with positive εHf (T) values recorded by most (∼90%) of the measured magmatic zircons from Iran suggest that the mantle input has played a significant and long-standing role in the magmatic genesis and crustal growth throughout the Mesozoic and Cenozoic evolution in this particular part of the Tethyan orogenic belt.